2018
DOI: 10.3389/fimmu.2018.02050
|View full text |Cite
|
Sign up to set email alerts
|

Complement After Trauma: Suturing Innate and Adaptive Immunity

Abstract: The overpowering effect of trauma on the immune system is undisputed. Severe trauma is characterized by systemic cytokine generation, activation and dysregulation of systemic inflammatory response complementopathy and coagulopathy, has been immensely instrumental in understanding the underlying mechanisms of the innate immune system during systemic inflammation. The compartmentalized functions of the innate and adaptive immune systems are being gradually recognized as an overlapping, interactive and dynamic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 178 publications
1
35
0
Order By: Relevance
“…It can be speculated that maybe upon reduced TAFI levels, missing inactivation of C3a and C5a may lead to an immunological imbalance and an excessive immunological reaction. As nicely reviewed and originally published by the expert group around Huber-Lang, anaphylatoxin C5a appears in the circulation of humans within 20 min post-polytrauma, and its levels have been related to the mortality rate [31,32]. That data indicated an almost synchronical rapid activation and dysfunction of the complement, suggesting a trauma-induced complementopathy early after injury [32].…”
Section: Discussionmentioning
confidence: 95%
“…It can be speculated that maybe upon reduced TAFI levels, missing inactivation of C3a and C5a may lead to an immunological imbalance and an excessive immunological reaction. As nicely reviewed and originally published by the expert group around Huber-Lang, anaphylatoxin C5a appears in the circulation of humans within 20 min post-polytrauma, and its levels have been related to the mortality rate [31,32]. That data indicated an almost synchronical rapid activation and dysfunction of the complement, suggesting a trauma-induced complementopathy early after injury [32].…”
Section: Discussionmentioning
confidence: 95%
“…Excessive complement activation after major trauma triggers SIRS that leads to MODS and death. Recently, multiple preclinical and clinical studies have demonstrated that complement activation after major trauma plays critical role in contributing to the SIRS and MODS in traumatic brain injury, chest trauma, musculoskeletal trauma, and polytrauma 28–31. Taken together, the complement activation products represent the main drivers of the systemic inflammation after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to traumatic or infectious insults results in an immediate activation of the complement cascade as major fluid defense system of innate immunity [48,299]. As nicely described by Huber-Lang, the complement system acts as a master alarm system during the molecular danger response after trauma and significantly contributes to the clearance of DAMPs and PAMPs [48,299].…”
Section: Complement Factorsmentioning
confidence: 97%
“…Exposure to traumatic or infectious insults results in an immediate activation of the complement cascade as major fluid defense system of innate immunity [48,299]. As nicely described by Huber-Lang, the complement system acts as a master alarm system during the molecular danger response after trauma and significantly contributes to the clearance of DAMPs and PAMPs [48,299]. Activation of complement in trauma patients has been verified by detection of elevated plasma C3a, C5a, and C5b-9 levels which correlate with disease severity [73,[300][301][302][303][304][305].…”
Section: Complement Factorsmentioning
confidence: 99%